Incorporating decentralized renewable energy in smart grid using Zigbeepro - Syed Zahurul, Islam (2016)
Distributed Renewable Generation (DRG) is one of the major components ofthe Smart Grid (SG) from where the real-time energy information is expectedto export to control center for demand management and energy forecasting.For this export service, low-powered and low-data rate ommunicationprotocol, e.g. ZigBeePRO is targeted for achieving the DRG communication requirement where reliability and critical demand of data delivery are not mandatory. In this thesis, the aim is to determine seasonal performance evaluation and energy yield modelling of the two photovoltaic (PV) modules, namely, Amorphous Silicon (A-Si) and Crystalline Silicon (C-Si) for Feed-in-Tariff (FiT) or DRG. Several other properties of the DRG solar environment,such as presence of various dielectric constant materials and uneven presence of obstacles are also considered in the analysis. To achieve these aims,shortest and strongest Received Signal Strength Indicator (RSSI) weighted path signal of ZigBeePRO is modelled relying on a real test-bed, 35kW solar DRG at Universiti Putra Malaysia (UPM). ZigBeePRO radio, Waspmote embedded board, and electrical and environmental parameters’ measurement sensors are coalesced into a sensor-node which are installed at the existing 10kW UPM solar DRG site. Based on the seamless acquiring and importing of these parameters from the DRG site to the control centre, the two types of PV modules’ performance are analysed which show significant variations in energy yield in tropical Malaysia. Moreover, the performance of data collection also shows that ZigBeePRO is recommended over ZigBee S1 for this specific purpose of SG where there is no strict-time and high demanding requirement of data delivery.